Analyzing gravastar structure with the Finch-Skea metric in extended modified symmetric teleparallel gravity - Iqra Ibrar; M. Sharif (Nuclear Physics B)
This study analyzes the physical features of a gravastar within the f(Q,T) gravity framework, where Q is the non-metricity scalar and T is the trace of the energy-momentum tensor. Gravastars present a viable alternative to black holes, featuring a central de Sitter core, a surrounding thin shell and a dynamic layer in the Schwarzschild exterior that separates these two regions. Using the Finch-Skea metric, the necessary field equations for the core and shell are derived, while the Israel junction conditions maintain a seamless connection between the inner and outer regions. This work extensively explores crucial aspects such as energy distribution, proper length, energy conditions, entropy and the equation of state parameter. The model's stability is studied through the effective potential, redshift, causality conditions and adiabatic index. Our results highlight the essential role of modified gravity in maintaining the structural viability and stability of gravastars.